Dual microphone solution for acoustic feedback cancellation for assistive listening - Nakagawa, Carlos; Nordholm, Sven; Yan, Wei-Yong (The Institute of Electrical and Electronics Engineers, 2012)
The method proposed in this paper improves the identification and cancellation of the feedback path by making the adaptive canceller robust against the impact of the desired speech signal. The proposed method allows for the canceller's coefficients to be continuously adapted allowing it to track variations in the feedback path even in the presence of the desired signal. It suggests the use of dual microphones and dual adaptive filters arranged in such a way that allows the speech signal to be identified and removed from the adaptation process. This results in a more robust solution which was verified by our experiments and evaluations. The perceptual evaluation of speech quality (PESQ) measure was also used to show that the proposed method results in better signal quality.